Asuhan Kebidanan Antenatal Pada Ny “S” Dengan Hiperemesis Gravidarum Tingkat I di Rumah Sakit Bhayangkara Kota Makassar - Siska, Siska; Nurhaedah, Nurhaedah; Ekawati, Nur; Hariati, Andi; Aotari, Wanti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Data obtained at the South Sulawesi Provincial Office of the number of maternal deaths in 2014 as many as 77 people with the most common cause is bleeding which is 40 people (51.94%), hypertension in pregnancy 21 people (27.27%), infection 1 person (1.29%) and other causes 15 people (19.48%). Data obtained from the Medical Record of Bhayangkara Makassar Hospital from the period January to December 2017 the incidence of Hyperemesis Gravidarum 10 people out of 450 (2.22%) while January to December 2018 the incidence of Hyperemesis Gravidarum 4 people out of 240 pregnant women (1.67%). The aim is to carry out midwifery care on Mrs.